POLÍTICAS PÚBLICAS DE EMPREGO PARA POPULAÇÃO JOVEM NO BRASIL NO PERÍODO NEOLIBERAL: gênese, desenvolvimento e perspectivas - MELO, Wagna Maquis Cardoso de (2012)
Study of public employment policies for youth in Brazil developed in the neoliberal period. This is on the understanding that young people affected by the current employment policies are marginalized youth of the social structure, as well as those victimized by the lack of jobs, are devoid of rights guarantees in the fields of health, education, leisure, culture and so on. Analyzes historically higher unemployment in this population crisis scenario of employment and social policies of fragmentation. Recover the reflections existing in Brazil on the determinants of unemployment of young people, compounded over the years 1990. Rescue, historically, social demands juveniles in Brazil unleashed over the years 1985 to 2005, a period delimited between the first international intervention on the issue of social vulnerability of youth and the creation of the National Youth Secretariat in Brazil. Weave themselves some considerations about employment policies designed for the general population victimized by unemployment, by PLANFOR inaugurated in 1996, guided, above all, the assumption of scarcity of skilled labor to meet the new demands of the labor market, against the restructuring process. Lectures that address the lack of job opportunities, even if the actions taken are active die eventually assuming a compensatory character, since they are based on the ideology of qualification as a solution to cope with unemployment this population. We conclude, from the viewpoint held by many authors, that current public policies for youth are insufficient to reduce unemployment levels in this population, because they are faced with structural limitations expressed in the scarce job opportunities resulting from the path followed by national economy and the restructuring process whose effects cover all the young Brazilians, even the best social position, or higher education. Finally, we demonstrate that even in periods of economic growth and recovery youth do not experience immediate answers in terms of integration into the labor market arises from the perspective of those policies to qualify for unemployment.